An Innovative Approach for Wastewater Management Using Staged Onsite Wastewater Treatment System Positioned on Environmental Floors of Multi-Storey Building - S. V. Dewalkar; S. S. Shastri (Challenging Issues on Environment and Earth Science Vol. 4, 2021)
About 30% of the existing wastewater treatment systems of Indian housing societies are observed as non-functional and while looking at statistics of their operating efficiency, the huge cost is associated with their operation and maintenance. To tackle these problems treatment systems are needed to be on-site, cost-effective, and self-sustainable, delivering chemical-free treated effluent that would be entirely harmless to nature and residents. Decentralized onsite integrated waste management system (DOSIWAM) is naturally operating, relatively simple and can be designed to provide low-cost sanitation and environmental protection with additional benefits from the reuse of water and biogas. In the current research, Effective positioning and modeling of the non-mechanised, gravity-governed wastewater treatment system is carried out at refuge floor which is coined to be proposed as “environmental floor” for G+32 storeyed residential building. To assess the viability of the treatment system and quantify the benefits coming from it, a comparative analytical analysis for structural and seismic response of both structures (with and without environmental floors) is conducted. The behavioral response of the structures studied from the obtained results, clearly states that the locations of DOSIWAM are safe. With minor changes in design and construction, the system would be effective in urban areas, especially for multi-storey buildings.